Biosilica as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids. Issue 14 (1st April 2015) - Mahanta, Abhijit; Adhikari, Pooja; Bora, Utpal; Thakur, Ashim Jyoti
Graphical abstract: Abstract: A mild and efficient protocol for the conversion of arylboronic acids to phenol via ipso -hydroxylation has been developed using aqueous hydrogen peroxide as oxidant and biosilica as heterogeneous catalyst. The recyclability of the catalyst is also evaluated and could be reused up to six consecutive cycles without a significant loss in catalytic activity.